A view to kill - Holstein, Thomas W. (BMC biology, 2012)
Genome and proteome data from Hydra magnipapillata have opened the way for the molecular analysis of an ancient nervous system, which includes stinging cells, an unusual neurosensory and neurosecretory cell type. They hold some surprises for the mechanisms and evolution of sensory transduction that could not have been anticipated from what has been learned from flies and vertebrates. Research in BMC Biology now implicates the ancient opsin-mediated transduction pathway in the neuronal control of stinging cell discharge.
Gesehen am 15.02.2017